Loneliness, Social Support, Social Trust, and Subjective Wellness in Low-Income Children: A Longitudinal Approach - Hanife Akgül; Ahmet Zeki Güven; Sibel Güven; Müyesser Ceylan (MDPI AG, 2023)
The progress and development of society in every sense is possible by raising healthy individuals. To do so, it is necessary to ensure the physical and mental development of children in a healthy way. There are many variables that affect the physical and mental development of children. These variables are affected by individual factors, social structure, social interactions and cultural values. In addition, when these factors interact with each other, their effect on behavior and well-being may increase. Undoubtedly, one of the primary factors negatively affecting a child's physical and psychological development is the adverse economic conditions and hardships experienced by his/her family and consequently, by the child. Increasing poverty hinders children's access to resources, and thus negatively affects their mental health as well as their physical development. Furthermore, positive economic conditions pave the way for an improved environment, better nutrition, higher-quality education, elevated social status, more friends, reduced feelings of loneliness, and increased social support and trust and all of these positively contribute to psychological well-being. Therefore, based on the conviction that early interventions can be protective and screening is needed to determine the proper intervention, this study aims to investigate the relationship between psychological well-being, loneliness, social support and social trust, all of which affect the psychological health of children living in economically disadvantaged families. To this end, answers to the following questions were sought. Is there a significant relationship between the loneliness, social support, social trust and psychological well-being of the children from low-income families? Do the feelings of loneliness, social support and social trust of the children from low-income families significantly predict their psychological well-being?